Optimization of Coating Formula of White Pomegranate Peel Extract (Punica granatum L.) Film Coated Tablet Using Kollicoat Protect - Stefani Luke; Martha Ervina; Lannie Hadisoewignyo (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2021)
White pomegranate peel has many kinds uses, one of them as antimalaria. The unpleasant appearance and bitter taste of white pomegranate peel tablet can be covered by film coated using Kollicoat Protect. This research aimed to determine the effect of concentration and type of solvent used as a coating on the physical properties of the coated tablets and determine the optimum formula. Tablets were made using direct compression method and then coated using Kollicoat Protect. The optimization of coating formula was performed using a factorial design with design expert software ver 10.0. Responses used were tablet hardness, friability, disintegration time and increasing tablet mass. The results of this study showed that Kollicoat Protect cause increase of weight gain tablets and decrease the tablet friability, but prolong the disintegration time of tablets and decrease the tablet hardness while type of solvent can increase of weight gain tablets, tablet hardness, and decrease the tablet friability but prolong the disintegration time of tablets. The optimum combination formula was Kollicoat Protect at 13.6% and combination of water:alcohol (1:0.863) (w/v) with a theoretical response to weight gain of 2.340%; hardness 7.950 kp; friability 0.022%; and disintegration time 20.938 minutes.